2007
DOI: 10.1097/01.pcc.0000257098.32268.aa
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of the Behavioural Observational Pain Scale for postoperative pain measurement in children 1???7 years of age*

Abstract: With BOPS, the caretaker can evaluate and document pain with high reliability and validity and thereby improve postoperative pain treatment in preschool children. The simple scoring system makes BOPS easy to incorporate in a postoperative unit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 24 publications
0
38
1
3
Order By: Relevance
“…Anestesiologista 3 A validade de constructo foi determinada a partir da observação das alterações nos escores de dor em resposta à administração de analgésicos, método este extensivamente utilizado no processo de validação de escalas de dor em pediatria (Bullock e Tenenbein, 2002;Manworren e Hynan, 2003;Hesselgard et al, 2007). Na veterinária, a avaliação do constructo tem se focado nas alterações dos escores de dor ao longo do período pós-operatório (Morton et al, 2005;Murrel et al, 2008) (Farrar et al, 2000; ou 55% (Klooster et al, 2006) já apresenta significado clínico.…”
Section: Item Da Escalaunclassified
“…Anestesiologista 3 A validade de constructo foi determinada a partir da observação das alterações nos escores de dor em resposta à administração de analgésicos, método este extensivamente utilizado no processo de validação de escalas de dor em pediatria (Bullock e Tenenbein, 2002;Manworren e Hynan, 2003;Hesselgard et al, 2007). Na veterinária, a avaliação do constructo tem se focado nas alterações dos escores de dor ao longo do período pós-operatório (Morton et al, 2005;Murrel et al, 2008) (Farrar et al, 2000; ou 55% (Klooster et al, 2006) já apresenta significado clínico.…”
Section: Item Da Escalaunclassified
“…Esta última escala no tiene un punto de corte inequívoco; sin embargo, en distintos estudios se ha usado <7 para definir la ausencia de dolor. [7][8][9][10][11][12] Para dar de alta al paciente de la sala de procedimientos se utilizaron criterios objetivos de alta según el puntaje de Aldrete modificado, 8 que evalúa distintos parámetros clínicos, otorgando un puntaje máximo de 14: paciente sin efecto de sedación (Tabla 3).…”
Section: Resultsunclassified
“…7,9,14 Al aplicar ambas escalas en este grupo de pacientes, se vio que la mayoría de los procedimientos, de acuerdo con los puntos de corte designados, contaron con sedación profunda adecuada y analgesia adecuada.…”
Section: Discussionunclassified
“…7,9,14 When these two scales were applied to this group of patients, our team observed that most procedures achieved adequate deep sedation and analgesia, according to the specified cut-off points.…”
Section: Discussionmentioning
confidence: 99%
“…The CHEOPS scale does not have an unequivocal cut-off point; however, a score of <7 has been used in different studies to define the absence of pain. [7][8][9][10][11][12] For the decision to discharge the patient from the procedure ward, the objective discharge criteria of the modified Aldrete score were used, 8 which assesses different clinical parameters, with a maximum score of 14: patient with no sedation effect ( Table 3). For this study, adequate analgesia was defined as a score of <7.…”
Section: Original Articlementioning
confidence: 99%